Antimicrobial activities of stembark and wood extracts from Nuclea subdita against pathogenic microorganisms - Jamaluddin, Fatin Ruzanna; Lee, Seng Hua; Ashaari, Zaidon; Wahab, Razak; Mohd Daud, Jamaluddin (Malaysian Society for Microbiology, 2015)
The aim of the study was to investigate the antimicrobial activity of Nuclea subdita (Korth) Steud against six pathogenic microorganisms. Methodology and results: Young and maturedtrees ao N. subdita were cut and separated into bark and wood parts, respectively, prior to extraction process. Phytochemical screening tests, antimicrobial activity, minimal inhibitory concentration (MIC) and minimal bacterial concentration (MBC) values were determined. Preliminary screening for phytochemical components showed that both young and matured tree had similar constituents. Extracts from matured tree showed more potency in terms of the zones of inhibition sizes than the young tree. Extract of N. subdita was more potent to both marine bacteria, Vibrio parahaemoliticus and V. alginolyticus, while Candida albican and Aspergillus niger were resistant to it. The sensitivity test showed that 500 ug/mL is the optimum concentration for extract of bottom sapwood of mature tree to act as bactericidal. Conclusion, significance and impact study: The results from this study suggest that N. subdita bark and wood extracts may serve as potential source of antimicrobial agents for future development in medicine applications.